Life cycle of Amblyomma mixtum (Acari: Ixodidae) parasitizing different hosts under laboratory conditions. - PIÑA, F. T. B. (2017)
Amblyomma mixtum is a tick species in the Amblyomma cajennense complex. The known geographic range of A. mixtum extends from Texas in theUSAto western Ecuador and some islands in the Caribbean. Amblyomma mixtum is a vector of disease agents of veterinary and public health importance. The objective of this study was to describe the life cycle of A. mixtum under laboratory conditions. Bovines, rabbits and sheep were infested with larvae, nymphs, and adult ticks under controlled conditions to assess several biological parameters. Eggs, larvae, nymphs and adults were kept in an incubator (27 C temperature and 80% relative humidity) when they were off the host. The average life cycle of A. mixtum was 88 and 79 days when fed on rabbits and cattle, respectively. Sheep were found to be unsuitable because no ticks attached. The rabbit is a more practical host to maintain a colony of A. mixtum under laboratory conditions. The data from this study can be considered as an example for the life cycle of A. mixtum. However, caution must be exercised when making comparisons to the biology of A. mixtum in its natural habitat.